Penggunaan Media Rosetta Stone melalui Metode Dynamic Immersion untuk Meningkatkan Kosakata Bahasa Inggris Siswa Menengah Pertama - Nursaima Harahap; Siti Meutia Sari; Yulia Rizki Ramadhani (Jurnal Education and Development, 2019)
The aim of this research is to describe the influence of Rosetta Stone media and applying the Dynamic Immersion method to improving students' English vocabulary. The Rosetta Stone a is a visual and computer based media. This media displays two-way communication, so it can improve student interactivity. The preferred method is Dynamic Immersion which is without English translation, only in the form of visuals or images, so it is expected that the students' brains are immediately used to associating English vocabulary with visual images. This reseach using classroom action research (CAR) when the students in SMP N 3 Padangsidimpuan as a research subject which amounted to 33 students. Data are collected using observation sheets, also evaluation tests. The results of the study increased from the cycle I to cycle II.